Military review in the context of cyber-warfare. Article 36 of 1977 additional protocol i in practice - Łasa, Robert (Wydawnictwo Uniwersytetu Rzeszowskiego, 2023)
The purpose of this study is to present the modern challenges facing the armed forces in examining the legality of means and methods of warfare, especially means and methods of warfare used in cyberspace. The study presents the method of military review in the context of Art. 36 of Additional Protocol I of 1977 and the need to extend it to modern means and methods of warfare. In addition, the positions of the states on the application of the military review to means and methods of warfare in cyberspace are presented.

Celem niniejszego opracowania jest przedstawienie współczesnych wyzwań stojących przed siłami zbrojnymi w zakresie badania legalności uzbrojenia, w szczególności środków i metod walki używanych w cyberprzestrzeni. W artykule omówiono metodę badania legalności uzbrojenia w kontekście art. 36 Protokołu dodatkowego I z 1977 r. oraz konieczność jej rozszerzenia na nowoczesne środki i metody walki. Ponadto zaprezentowano stanowiska poszczególnych państw odnośnie do stosowania przeglądu uzbrojenia do środków i metod walki w cyberprzestrzeni.
Przegląd uzbrojenia w kontekście cyberwojny. Artykuł 36 protokołu dodatkowego i z 1977 r. W praktyce
Keywords: military review; international humanitarian law; armed conflict; means and methods of warfare; przegląd uzbrojenia; międzynarodowe prawo humanitarne; konflikt zbrojny; środki i metody walki